2021
DOI: 10.3390/biology10121223
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of Environmental DNA Based Methods (Sensu Stricto) in Biodiversity Monitoring and Conservation: A Review

Abstract: Recently developed non-invasive environmental DNA-based (eDNA) techniques have enlightened modern conservation biology, propelling the monitoring/management of natural populations to a more effective and efficient approach, compared to traditional surveys. However, due to rapid-expansion of eDNA, confusion in terminology and collection/analytical pipelines can potentially jeopardize research progression, methodological standardization, and practitioner adoption in several ways. Present investigation reflects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 122 publications
0
13
0
Order By: Relevance
“…(Matsukura & Wada, 2017). Furthermore, the use of Environmental DNA or "eDNA" has provided a promising non-invasive/ non-destructive approach for quick monitoring (Taberlet et al, 2012;Banerjee et al, 2021). In fact, monitoring approaches using eDNA based methods have gained popularity amongst ecologists, conservation biologists, and wildlife managers as it generally: (i) does not require direct observation or handling of organisms (Taberlet et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Matsukura & Wada, 2017). Furthermore, the use of Environmental DNA or "eDNA" has provided a promising non-invasive/ non-destructive approach for quick monitoring (Taberlet et al, 2012;Banerjee et al, 2021). In fact, monitoring approaches using eDNA based methods have gained popularity amongst ecologists, conservation biologists, and wildlife managers as it generally: (i) does not require direct observation or handling of organisms (Taberlet et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, monitoring approaches using eDNA based methods have gained popularity amongst ecologists, conservation biologists, and wildlife managers as it generally: (i) does not require direct observation or handling of organisms (Taberlet et al, 2012). This approach thus provides detection (presence/absence), relative abundance, distribution, and even species interaction data in a fast, cheap, and non-invasive manner (Qu & Stewart, 2019;Banerjee et al, 2021); (ii) is found to be equally (or more) accurate as compared to conventional methods for various species (Kuzmina et al, 2018)-especially in circumstances of low abundance, extreme habitats, phenotypic plasticity, juvenile stages, and during the early stages of invasion; and (iii) records a higher diversity of taxa in a single sampling than morphological and DNA-based (tissue samples) methods (McElroy et al, 2020;Fediajevaite et al, 2021). In fact, eDNA-based methods are well known for detecting invasive species early during colonization (Ficetola et al, 2008), and recent optimization/standardization practices have improved their accuracy for more reliable detection of targeted species, reinforcing eDNA's trustworthiness for field applications (Deiner et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…An additional cause to such patterns could also be explained due to amplification efficiency. Sequence abundance output is subjected to amplification biases due to primer efficiency (Kelly et al, 2019), especially when using universal primers, where selected taxa have a higher match with the primer than others (Banerjee et al, 2021). Such biases influence the commonness of the species, which can lead to divergence from the true species as drivers of differences between ecosystems (since low amplification species will be encouraged to be the species indicators).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the large number of unknowns about the fate of DNA, other authors have noted that there is not yet enough methodological validation of sample processing steps (i.e., filtration, preservation, amplification and sequencing) before sequences are read and aligned [4,35]. Presently, frequently cited problematic issues in eDNA studies are the lack of standardization of the methods, incompleteness of referenced sequence database, and lack of appropriate contamination controls, or sensitivity measures [36,56,57]. Together these create many theoretical and analytical challenges for the interpretation of eDNA results within EIA.…”
Section: The Fate Of Dna In Aquatic and Marine Environmentsmentioning
confidence: 99%